Menggali Konsep Keadilan Dalam Poligami: Studi Terhadap Nilai Moral Dalam Masyarakat Muslim - Fuadi, Ahmad; Anggreni, Devi; Fitriyani, Fitriyani (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
Law No. 1 of 1974 stipulates that the primary principle of marriage in Indonesia is monogamy, while polygamy is permitted only in specific situations and under very strict conditions. In the Compilation of Islamic Law, provisions regarding polygamy are regulated in Articles 55 and 56, which state that polygamy is only allowed under particular circumstances and must fulfill several predetermined requirements. Although legal regulations governing polygamy exist, its practice continues to raise various issues for certain groups. This study employs a normative juridical approach, utilizing secondary data obtained through literature studies. The research specification is descriptive-analytical, describing the applicable legislation, linking it to legal theories, and comparing it with its practical implementation. The findings show that polygamy in Islam is only permitted as a solution in emergency situations, not as a choice without a clear reason. This allowance aims to protect marginalized women or children in need of care. Polygamy must be carried out responsibly, based on humanitarian objectives, and requires the husband's ability to act fairly and wisely, not merely driven by personal desires.